A New Action-based Dataset of Fiscal Consolidation in Latin America and the Caribbean - David, Antonio (IMF Working Papers; Working Paper ;, 2018)
This paper presents a new database of fiscal consolidations for 14 Latin American and Caribbean economies during 1989-2016. We focus on discretionary changes in taxes and government spending primarily motivated by a desire to reduce the budget deficit and long-term fiscal health and not by a response to prospective economic conditions. To identify the motivation and budgetary impact of the fiscal policy changes, we examine contemporaneous policy documents, including Budgets, central bank reports, and IMF and OECD reports. The resulting series can be used to estimate the macroeconomic effects of fiscal consolidation for these economies.